PEMBERDAYAAN KAMPOENG RABBIT’S UNTUK MEWUJUDKAN DAERAH TENAYAN RAYA MENJADI OBJEK WISATA - Sri Nanda; Ranti Darwin (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2019)
Kampoeng Rabbit’s is one of the new tourist attractions established in the city of Pekanbaru about 2 years ago precisely on February 2, 2017 which has a land area of 1190M2 and is located on Jalan Kenanga, Tenayan Raya, this place is a tourist magnet in the Pekanbaru area, especially the Tenayan Raya area. The objectives of this program are: 1) Designing Kampoeng Rabbit’s management to be a family-friendly tourist destination. 2) Building a plan in developing Kampoeng Rabbit’s in order to become a tourism place that has prospects going forward. Implementation methods of this activity include initial survey activities, problem identification, needs analysis, determination of target audiences, program formulation, formulation and measurement of program success indicators, program implementation, target audience development strategies, partnership and partnership, monitoring and evaluation, results workshop with stakeholders, reporting, and updating post-program target data per 4 months. The results of the activities for the time being are: 1) The people of the Region of Tenayan Raya, especially on Jalan Kenanga, Kelurahan Mentangor Kec. Tenayan Raya can directly feel the impact of this Kampoeng Rabbit’s tour. 2) This tourist spot is an educational tourist spot that provides a family-friendly atmosphere that is suitable for extended family trips. 3) Increase the income of Kampoeng Rabbit’s manager. 4) Making Kampoeng Rabbit’s attraction can be known and known by many people, especially outside the Pekanbaru area. 5) With the cooperation of the owner of the tourist attraction and local community leaders such as the Head of RT and RW Chairman can develop Kampoeng Rabbit’s empowerment program to make the Tenayan Raya area a family-friendly tourist attraction.